Escaping domestic violence: Empowering women through employment, earnings and wealth in India? - Aparna Mathur; Sita Nataraj Slavov (American Enterprise Institute (AEI), 2013)
Using data from two detailed, nationally representative, household datasets – the National Family Health Survey and the India Human Development survey – we explore whether women who are economically empowered (through work, earnings, or wealth) are less likely to experience domestic violence. We find that, while working women may be at a greater risk of violence, higher earnings are associated with a reduction in violence. Although these findings are informative, they do not necessarily establish a causal link between economic empowerment and violence. To test for causality, we exploit arguably exogenous variation in state laws designed to equalize the inheritance rights of sons and daughters. Additional variation comes from the fact that these state laws did not apply to some women based on their religious affiliation and date of marriage. We find some evidence that women who were subject to these laws are less likely to report being victims of domestic violence.
Keywords: F; 330; India; domestic violence; women in the workplace